2020
DOI: 10.1108/jkm-04-2020-0243
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing members’ knowledge sharing and creative performance in coworking spaces

Abstract: Purpose Coworking spaces (CWS) are a globally increasing phenomenon of new shared work environments used by freelancers, entrepreneurs and small companies that often work in information technology and creative industries. The purpose of this study is to examine coworkers’ knowledge sharing (KS), focusing on attitude, behavior and individual creativity. Several theoretical perspectives are deployed for factors influencing KS. Design/methodology/approach A research model is developed and tested, relying on a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 131 publications
3
51
0
4
Order By: Relevance
“…While the five core values loaded on one factor and uni-dimensionality could be established, the value “collaboration” is a discriminator for those working alone and team workers in the CWS. This is also a finding of Rese et al ( 2020 ) confirming member heterogeneity (Bouncken and Reuschl 2018 ). In addition, we contribute to research on network structure and similarly to research in other contexts.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…While the five core values loaded on one factor and uni-dimensionality could be established, the value “collaboration” is a discriminator for those working alone and team workers in the CWS. This is also a finding of Rese et al ( 2020 ) confirming member heterogeneity (Bouncken and Reuschl 2018 ). In addition, we contribute to research on network structure and similarly to research in other contexts.…”
Section: Discussionsupporting
confidence: 84%
“…Bouncken and Aslam ( 2019 ) confirmed that geographical proximity fosters knowledge sharing processes by coworkers while relying on in-depth qualitative interviews. Knowledge exchange processes and related antecedents, such as trust or community, have been studied by Bouncken and Reuschl ( 2018 ) on a conceptual level and Rese et al ( 2020 ) empirically. The latter found a positive relationship between attitudinal and intentional belief to share knowledge and individual creativity.…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…The research by A. Rese, C. S. Kopplin, and C. Nielebock discovers the meanings of coworking space (CWS) [20]. A. Rese, et al studied the exchange of knowledge among col leagues, with a special focus on attitudes, behavior, and indi vidual creativity.…”
Section: Organization Of Knowledge Management Culture In the Modern System Of Higher Education At The Technological Levelmentioning
confidence: 99%